Determinantes de la diversificación de exportaciones en Sudamérica: Un análisis con datos de panel - Diego Andrés Pe\~naranda Molina (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2021)
– Numerous recent studies argue that higher levels of export diversification generate economic growth in developing economies. This study reviews relevant export statistics for a set of South American countries for 1995-2017 and seeks to approximate the fundamental determinants of export diversification in these countries as measured by the Herfindahl-Hirschman, Theil, and Economic Complexity indices. For this purpose, three econometric models are constructed using panel data: Pooled Ordinary Least Squares (POLS), Generalized Method of Moments in Differences (DIF-GMM) and System of Generalized Method of Moments (SYS-GMM). The results point to four variables that maintain a positive relationship and four that maintain a negative relationship with export diversification. In the first group are primary education, economic freedom, total investment and population size. In the second, are the variables associated with foreign direct investment, international commodity prices, public spending and mediterraneity. In addition, based on these results, some policy recommendations are outlined towards greater export diversification in the region.
Keywords: F14; C23; 330; Empirical Studies of Trade; Panel Data Models